Practicing teaching librarian in public higher education: what is lacking in the profession? - Dzulkipli, Mohd Razif; Abu, Roziya; Shaifuddin, Norshila (Penerbit Universiti Teknikal Malaysia Melaka, 2024)
This article aims to promote one of academic librarian’s role in higher education and to dig out what is being left out in the librarianship profession, the unacknowledged hero teaching librarian. Placed in the heart of library’s main function which is to educate and teach users in information literacy, it is a crucial position in all academic libraries. The article is to highlight issues surrounding this specific practice in librarianship and recommendation that might solved the issue based on academic literature. Academic librarian is a generic term used to represent librarian who works in the library in higher education environment, but they were segmented into roles and function based on management’s decision and needs such as automation librarian is an academic librarian who take charge and manages all matters related to information technology in the library. A teaching librarian is an academic librarian who teaches and educates users of the library in information literacy programs or classes.